The adoption of photovoltaic micro production systems in Finland - Nousiainen, Juho (2016)
A sustainable supply of energy is one of the most important requirements in order to achieve sustainable development. By using renewable resources society is not dependent on depleting reserves, but instead can have an inexhaustible source of clean energy. The rapid development of photovoltaics has led to lowered prices and increased efficiency making them more attractive alternative as a source of household electricity. Although governments play a key role in setting the constraints of how renewable energy is adopted, the wide-spread adoption of distributed electricity production ultimately depends on consumer decisions to buy them. This study examined the adoption process of photovoltaic micro production sys- tems in Finland. Furthermore, it concentrated on the characteristics and differences between adopters and non-adopters of photovoltaic systems and tried to recognize the barriers for adoption as well as factors that encourage adoption. The theoretical framework was built on Diffusion Of Innovations theory which has been previously utilized to model the diffusion of photovoltaic systems. This approach seeks to explain how, why and at what rate new ideas, products and technologies spread through society. The results of this study show, that the reasons and barriers for adoption vary greatly between individuals and the adoption process is far from straightforward. The most common barriers for adoption was economic terms such as high price and long payback time of the initial investment, greater complexity compared to electricity from the grid and fairly low level of knowledge of photovoltaic micro production. Moreover, factors that lead to adoption of photovoltaic systems was economic savings, necessity and the values of the adopter. Finally, when comparing the differences of adopters and non-adopters of photovoltaic systems of this study, they seem to differ in for example demographic characteristics and values. The motivation for this research came from the author's own interests and there was no commissioning company for this Master’s Thesis.